Chromosomal Aneuploidy Associated With Clinical Characteristics of Pregnancy Loss - Gu, Chongjuan; Li, Kuanrong; Li, Ru; Li, Ling; Li, Xiaojun; Dai, Xinyu; He, Yaojuan (Frontiers in Genetics, 2021)
Objective Embryonic aneuploidy is found in about half of sporadic pregnancy losses and the associations between the chromosomal aneuploidy and clinical characteristics of pregnancy loss remain unclear. The aims of this study were to evaluate the associations between chromosomal aneuploidy of products of conception (POC) and clinical features of pregnancy loss. Methods We conducted a retrospective cohort study including 1,102 women experienced singleton pregnancy loss and underwent chromosomal microarray analysis (CMA) detection of POC in our hospital. The results of molecular karyotypes and clinical features including maternal age, history of pregnancy loss, gestational age, vaginal bleeding and ultrasonographic findings were extracted from the medical records. χ2 test was used to compare categorical data between groups. Results 631 (57.26%) POC specimens were detected to be chromosomal aneuploidy. Aneuploid rates were significantly higher in women >35 years (P < 0.001) and pregnancy loss <11 gestational weeks (P = 0.044), but the rates of sex chromosome abnormalities and triploid were significantly higher in women ≤35 years (P < 0.001, P = 0.002) and the rates of viable autosomal trisomy and sex chromosome abnormalities were significantly high in those women with pregnancy loss ≥11 weeks (P < 0.001, P < 0.001). Aneuploid rate was overall similar between the sporadic and the recurrent pregnancy loss (RPL) (P = 0.404), but the rate of sex chromosome abnormalities was higher in women with sporadic pregnancy loss (P = 0.03). Aneuploid rates were higher in subjects with yolk sac or embryo than in those without (P < 0.001 and P = 0.001). Conclusion Advanced maternal age is mainly associated with autosomal trisomy, while sex chromosome abnormalities and triploid might be more likely to occur in younger women. Aneuploidy rates might be no association with previous pregnancy loss except for sex chromosome abnormalities. Pregnancy loss without yolk sac or embryo might be less related to embryonic aneuploidy, and other factors should be emphasized.